2022
DOI: 10.1088/2515-7620/ac9bd7
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous warming impacts of desert wind farms on land surface temperature and their potential drivers in Northern China

Abstract: To address rapid climate change, wind energy has been widely developed in China in the last two decades. However, wind farm (WF) turbulence effects can change the local climate by redistributing temperature, humidity, and heat fluxes. Previous studies indicate that WFs can significantly increase nighttime land surface temperature (LST); however, their conclusions are mainly derived from individual WFs and ignore heterogeneous impacts among multi-WFs in China. Another large source of uncertainty is that the WFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Although in situ data monitoring has the advantages of high data accuracy and distinctive features, it is limited in scale and has a major disadvantage, especially in assessing the ecological and climatic impacts of onshore wind farms in a large-scale context. In situ data monitoring can provide reliable information for the inversion of remotely sensed data, such as inversely assessing near-surface temperatures at different times (Walsh-Thomas et al, 2012; Zhou et al, 2012; Zhou et al, 2013; Harris et al, 2014; Slawsky et al, 2015; Chang et al, 2016; Liu et al, 2021b; Luo et al, 2021; Liu et al, 2022a; Ma et al, 2022; Qin et al, 2022), vegetation indexes (Li et al, 2016; Tang et al, 2017; Xia and Zhou, 2017; Wu et al, 2019; Liu et al, 2022b; Aksoy et al, 2023), landscape patterns (Zhang et al, 2016; Diffendorfer et al, 2019; Guo et al, 2020) and other indicators in order to assess the impacts of onshore wind farms on the localized eco-climate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in situ data monitoring has the advantages of high data accuracy and distinctive features, it is limited in scale and has a major disadvantage, especially in assessing the ecological and climatic impacts of onshore wind farms in a large-scale context. In situ data monitoring can provide reliable information for the inversion of remotely sensed data, such as inversely assessing near-surface temperatures at different times (Walsh-Thomas et al, 2012; Zhou et al, 2012; Zhou et al, 2013; Harris et al, 2014; Slawsky et al, 2015; Chang et al, 2016; Liu et al, 2021b; Luo et al, 2021; Liu et al, 2022a; Ma et al, 2022; Qin et al, 2022), vegetation indexes (Li et al, 2016; Tang et al, 2017; Xia and Zhou, 2017; Wu et al, 2019; Liu et al, 2022b; Aksoy et al, 2023), landscape patterns (Zhang et al, 2016; Diffendorfer et al, 2019; Guo et al, 2020) and other indicators in order to assess the impacts of onshore wind farms on the localized eco-climate.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the timing of warming showed that the warming effect of onshore wind farms on the near-surface is concentrated at night, and is not significant during the day (Ma et al, 2022; Qin et al, 2022). A few studies have suggested that the nighttime temperature base value decreased compared to the pre-construction period (Luo et al, 2021; Liu et al, 2022a). The results of onshore wind farm warming effects in relation to seasons are inconsistent, with most studies suggesting that warming is most significant in summer and fall (Chang et al, 2016; Liu et al, 2021b; Zhang et al, 2023).…”
Section: Impacts Of Onshore Wind Farms On Local Climatementioning
confidence: 99%
See 1 more Smart Citation